Defending tranexamic acid and sensible scientific clinical trial design - Bruce L. Davidson (Bleeding, Thrombosis and Vascular Biology, 2026)
Three recent clinical trial reports published in the New England Journal of Medicine (NEJM) appear to undermine reputed effectiveness of tranexamic acid (TXA) as a hemostatic drug. They found no value for TXA over placebo as they used TXA, and as they assessed the outcome [...]